Addition of basil leaf (Ocimum basicilum L.) extract to AndroMed® extender improved the quality of spermatozoa of frozen thawed Simmental bull semen - Aditya Irawan; Fajar Ramadhan Subiyantoro; Suherni Susilowati; Tri Wahyu Suprayogi; Sri Pantja Madyawati; Pudji Srianto; Nove Hidajati; Eduardus Bimo Aksono Herupradoto; Kadek Rachmawati (Ovozoa: Journal of Animal Reproduction, 2024)
This study aims to determine the best dose of basil leaf extract to add to AndroMed® semen extender to improve spermatozoa quality after freezing and thawing. This study used healthy, normal four-year-old Simmental bulls with good libido. The sample used was fresh semen from Simmental bull collected using an artificial vagina. This study used a completely randomized design (CRD) with three treatments and six replicates. Ejaculate that met the motility qualification of more than 70%, was divided into three groups, each extended in AndroMed® without the addition of basil leaf extract (T0), with the addition of 0.1% basil leaf extract (T1) and with the addition of 0.3% basil leaf extract (T2). Straw containing semen with 30 million spermatozoa/straw was processed using an IceCube automatic freezer (Minitube, Germany). The results showed that spermatozoa motility, viability, and spermatozoa plasma membrane integrity in the T2 group were higher (p <0.05) than those in the T0 and T1 groups, while spermatozoa morphological abnormalities in the T2 group were lower (p <0.05) than those in the T0 and T1 groups. There were no significant differences (p >0.05) in these parameters between groups T0 and T1. It could be concluded that the addition of 0.3% basil leaf extract to the AndroMed® extender could improve the quality of the semen of Simmental bulls after thawing.